Characteristics of leptospirosis cases, prevention and control managements 1955–2020, Guangzhou, China - Ziyi Zeng; Haiyan Chen; Jianmin Xu; Hao Zhang; Conghui Xu; Lirui Fan; Shouyi Chen; Kuncai Chen; Zhicong Yang; Yuehong Wei (One Health, 2023)
Background: Leptospirosis, which is an easily overlooked zoonotic disease, was once widespread in Guangzhou, China. However, due to the implementation of control measures, the number of cases is decreasing. Based on the characteristics of leptospirosis cases in Guangzhou, China, between 1955 and 2020, we describe the changes and achievements in prevention and control management strategies over that period. Methods: The development of the leptospirosis control system in Guangzhou occurred over three periods: Period I: 1955–1978; Period II: 1979–2000; and Period III: 2001–2020. Data about leptospirosis cases were obtained from the Guangzhou Center for Disease Control and Prevention (CDC) and national health departments. The demographic characteristics of leptospirosis patients were analyzed using descriptive statistics. Results: During Period I, only the Guangzhou CDC and medical institutions at every level participated in the leptospirosis control system. During Period II, additional types of organizations, including local CDCs, countryside committees, community committees, and the Patriotic Health Movement Commission, were involved in the control system. Additionally, strong links were established between different organizations. After entering Period III, an increasing number of departments joined the cooperation, and the management of human patients was expanded to include the management of host animals, and thus, the prevalence of leptospirosis was monitored and controlled in various ways. The leptospirosis control system in Guangzhou has been further improved. From 1955 to 2020, a total of 2501 leptospirosis cases were recorded in Guangzhou, and the number of cases decreased significantly over time, from 1608 (Period I) to 744 (Period II) and then to 149 (Period III). Conclusion: The improvements of the leptospirosis control system in Guangzhou that occurred over decades were associated with a marked decrease in the number of leptospirosis cases. Guangzhou's experience can provide guidance for other countries or cities around the world facing similar challenges.